1987
DOI: 10.1139/f87-086
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Size-Selective Mortality of Juvenile Sockeye Salmon (Oncorhynchus nerka) in Babine Lake, British Columbia

Abstract: Otolith – body length relations and back-calculation procedures were used to test the hypothesis that mortality of juvenile sockeye salmon (Oncorhynchus nerka) in Babine Lake, British Columbia, is size selective. Samples of the 1978 brood of sockeye were collected as fry from spawning tributaries as juveniles in the main basin, and as smolts at the outlet. Total otolith length was chosen as the most useful otolith dimension for back-calculation of fork length at emergence. Sockeye from the various tributaries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
90
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(101 citation statements)
references
References 14 publications
10
90
1
Order By: Relevance
“…Similarly, Jawad et al (2011c) showed the same results on Lutjanus benghalensis from Omani waters. The relationship between otolith length width and fish body proportions is related to the growth rate of the fish (Mugiya and Tanaka, 1992) and these relationship became curvilinear in some larval or juvenile fishes (West and Larkin, 1987), such curvilinearity was observed in the present study, but not in the previous similar studies on fishes from Oman (Al-Mamry et al, 2010;Jawad et al, 2011a;Jawad and Al-Mamry, 2012). Harvey et al (2000), Waessle et al (2003) and Battaglia et al (2010) have suggested that there is a possibility of getting error in the final results of the relationship between otolith dimensions and fish size due to changes in this relationship during the life history of the fish and as the fish length changes (Frost and Lowry, 1981;Hare and Cowen, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Jawad et al (2011c) showed the same results on Lutjanus benghalensis from Omani waters. The relationship between otolith length width and fish body proportions is related to the growth rate of the fish (Mugiya and Tanaka, 1992) and these relationship became curvilinear in some larval or juvenile fishes (West and Larkin, 1987), such curvilinearity was observed in the present study, but not in the previous similar studies on fishes from Oman (Al-Mamry et al, 2010;Jawad et al, 2011a;Jawad and Al-Mamry, 2012). Harvey et al (2000), Waessle et al (2003) and Battaglia et al (2010) have suggested that there is a possibility of getting error in the final results of the relationship between otolith dimensions and fish size due to changes in this relationship during the life history of the fish and as the fish length changes (Frost and Lowry, 1981;Hare and Cowen, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence from field-based research that enhanced growth rates in the larval stages play an important role in the survival rate of the early life stages of a wide range of species (Hovenkamp, 1992;West and Larkin, 1987;Post and Prankevicius, 1987;Wilson and Meekan, 2002;Rilling and Houde, 1999), showing their influence on recruitment success in a number of species (Campana, 1996;Bergenius et al, 2002). It is reasonable to expect a relationship between larval growth and recruitment because studies on other anchovy species have shown that survival within each ontogenic larval stage is size-specific and growth-dependent (Rilling and Houde, 1999), that mortality declines with age, and that one of its main causes is predation (Leak and Houde, 1987;Folkvord and Hunter, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…In general, salmon have very large eggs compared with other teleost fishes (9). The development of such large embryos is possible because the cold, highly oxygenated water counters the surface-to-volume constraint against large eggs and because size-selective predation (10) and competition favor large juveniles (11). Larger adult salmon have both larger and more numerous eggs than smaller salmon, but the energetic constraints on the female result in tradeoffs between egg size and egg number that are population-specific.…”
Section: The Biodiversity Of Bristol Bay Sockeyementioning
confidence: 99%